2022
DOI: 10.1159/000521284
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Data Differences in Perceived Control over Nursing Practice among Nurses Caring for Nursing Home Residents

Abstract: <b><i>Introduction:</i></b> Control over nursing practice is crucial for improved quality of life for nursing home (NH) residents. Nevertheless, little is known about the association of nurses’ demographic data with their perceived control over nursing practice in Jordan and beyond. Therefore, this study aimed at examining the differences in nurses’ levels of perceived control over nursing practice based on their demographic characteristics. <b><i>Methods:</i></b>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Nurses recognize the autonomous nature of their practice, as evidenced by their membership in accredited professional organizations, symbolizing the autonomy of the nursing profession. In contrast, Rababa et al (2022) found that nurses, according to gender, experience, and nursing home type, had low perceived control over nursing practice. This study provides insights into how nurses' sociodemographic and professional characteristics may impact their perceived control over nursing practice.…”
Section: Relationship Between Profile and Professional Autonomymentioning
confidence: 78%
“…Nurses recognize the autonomous nature of their practice, as evidenced by their membership in accredited professional organizations, symbolizing the autonomy of the nursing profession. In contrast, Rababa et al (2022) found that nurses, according to gender, experience, and nursing home type, had low perceived control over nursing practice. This study provides insights into how nurses' sociodemographic and professional characteristics may impact their perceived control over nursing practice.…”
Section: Relationship Between Profile and Professional Autonomymentioning
confidence: 78%